Pengaruh Penerapan Corporate Governance Terhadap Kinerja Keuangan - I Gusti Putu Wulandari; Partiwi Dwi Astuti (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2026)
The purpose of this study is to examine the influence of corporate governance implementation (board of commissioners, board of directors, firm size, and audit committee) on financial performance. The population in this study consists of insurance companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period, totaling 16 companies. The sample was selected using purposive sampling. The sample consists of 11 companies, and the collected data includes 55 financial statements across 5 reporting years. The data that can be utilized for analysis amounts to 51 financial statements. The analysis was conducted using multiple linear regression analysis with the Statistical Package for the Social Sciences (SPSS) program. The results indicate that the board of commissioners and the board of directors have an insignificant positive effect on financial performance. Meanwhile, firm size and the audit committee have a significant positive effect on financial performance.